Unlocking the Hidden Causes of Loan Defaults in Small Businesses: A Deep Dive into Financial and Market Challenges - Sindy Ayu Febrianti; Nur Suci I. Mei Murni (Center for Indonesian Accounting Studies, 2026)
Research Objective— This study aimed to identify the internal and external factors that cause problem loans among micro, small, and medium enterprises (MSMEs) in Sidoarjo, particularly those who are customers of the Anusapati Market Savings and Loans Cooperative. Research Method: This research uses a qualitative method with an interpretive approach and a phenomenological perspective. Data collection was conducted through in-depth interviews, direct observation, and documentation of MSMEs operating in the Deltasari Market area and experiencing problem loans. Research Results: The results indicate that problem loans arise from the interaction of various factors, particularly the priority of household needs that leads to payment delays, inadequate recording and management of business finances, decreased income due to increasingly intense business competition, and the influence of social and cultural conditions on financial decision-making. Research Findings: These findings highlight the importance of improving financial literacy and strengthening financial management skills among MSMEs and the role of mentoring financial institutions in minimizing the risk of non-performing loans and supporting business sustainability. Research Novelty – This study examines how non-performing loans among MSMEs are influenced by a combination of external and internal factors.